International Tourism, Foreign Monetary Policy, and Macroeconomic Growth: Evidence from Panel Data Analyses - Tecel, Ayhan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This study proposes a new research question that monetary policy changes by important central banks which are actors of the global financial system impact international tourist flows across continents through major macroeconomic mechanisms. As a first study, quarterly data is used to test the validity of this research question by considering the effects of the Federal Reserve (FED)’s monetary policy changes on the regional aggregate tourist flows around the World. Results of the first study confirm the long-term significant effects of the FED’s monetary policy actions on international tourist flows across continents. However, these effects are mixed in the directions (signs as positive or negative). This study proposes that the FED’s monetary policy changes indirectly impact tourist flows through changing exchange rates and therefore international prices, foreign direct investments in tourism sectors, and the mediation of financial system like domestic credits by the banking sector. Therefore, a second study is conducted to investigate the causal relations between tourism markets, FDIs, domestic credits, and real income growth in the case of the Mediterranean countries. Results reveal that long-term links and causal relations exist among the above-said variables. Furthermore, the tourism-led growth hypothesis is confirmed for the Mediterranean countries. Importantly, this study also finds that tourism is a significant driver for FDI and financial markets in these countries as well. These major results of this study provide important policy lessons for policymakers.

ÖZ: Bu çalışma uluslararası para piyasalarının aktörü durumunda olan önemli merkez bankaları para politikası değişikliklerinin, makroekonomik faktörler aracılığı ile uluslararası turist akışına olan etkisini inceleyen ve sahada yeni olan bir araştırma konusu önermektedir. İlk ampirik uygulamada FED para politikası değişikliklerinin dünya genelinde bölgesel tourist akışlarına olan etkisi çeyrek veri seti kullanılarak tahmin edilmiştir. Sonuçlar, FED para politikalarının kıtalararası turist akışlarına uzun dönemde anlamlı etki ettiğini göstermektedir. Fakat, bu etkilerin yönü (eksi veya artı) bölgeden bölgeye değişmektedir. Çalışma, FED para politikalarının turist akışlarına dolaylı etkilerinin döviz kurları, uluslararası fiyatlar, yabancı direkt yatırımlar, ve finansal piyasalar aracılığı ile gerçekleştiğini ortaya koymaktadır. Bu sebeble, bulguları desteklemek amacıyla ikinci ampirik bir çalışma daha yapılmıştır. İkinci çalışmada, Akdeniz ülkelerinde turist piyasaları, yabancı direkt yatırımlar, yurtiçi krediler ve reel gelir büyümesi arasındaki ilişkiler irdelenmiştir. Sonuçlar, bu değişkenler arasında uzun dönemli bir denge ve sebeb/sonuç ilişkilerin olduğunu göstermektedir. Ayrıca, çalışmada Akdeniz ülkeleri için turizm’e dayalı büyüme hipotezi desteklenmiştir. Önemli bir bulgu ise turizm sektörünün yabancı direkt yatırımlar ile finansal piyasalarının tetikleyicisi olduğu yönündedir. Bu çalışmada ortaya çıkan tüm bu temel bulgular politika üreticiler için önemli mesajlar içermektedir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Co-Supervisor: Prof. Dr. Turgay Avcı and Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Banking and Finance Department; International Tourism--Foreign Monetary Policy--Macroeconomic Growth; Tourism; Tourist Flows; Monetary Policy; Financial Markets; Foregin direct investment; Federal Reserve; Mediterranean